Analysis of Factors Affecting Receipt of The Zakat Funds - Monalisa, Mei (Efficient: Indonesian Journal of Development Economics, 2022)
The research was motivated by the potential receipt of the zakat fund in Indonesia, but when compared with the realization of its receipts, the revenue is still far from its potential. The purpose of this study was to determine and analyze the effect of the gold price, exchange rate, money supply, and inflation variables on the receipt of zakat funds period 2012-2019 at the Central Baznas in the long and short term. This study uses quantitive methods with time-series data types from January 2012 to December 2019. This study used is ECM (Error Correction Model) analysis. The results of this study are in the long term, variables gold price, money supply, and Inflation affect the receipt of zakat funds period 2012-2019 at the Central Baznas. The variable exchange rate has no effect on the receipt of zakat funds period 2012-2019 at the Central Baznas. In the short term, variables money supply and inflation affect the receipt of zakat funds period 2012-2019 at the Central Baznas. Variable gold price and the exchange rate have no effect on the receipt of zakat funds period 2012-2019 at the Central Baznas. Penelitian ini dilatarbelakagi oleh potensi penerimaan dana zakat di Indonesia yang ketika dibandingkan dengan realisasi penerimaannya, penerimaannya masih jauh dari potensinya. Tujuan penelitian ini adalah untuk megetahui dan menganalisis pengaruh variabel harga emas, nilai tukar, jumlah uang beredar dan Inflasi terhadap penerimaan dana zakat priode 2012-2019 di Baznas Pusat dalam jangka panjang dan pendek. Penelitian ini menggunakan menggunakan metode kuantitatif dengan jenis data time series dari januari 2012 sampai desember 2019. Metode analisis yang digunakan adalah analisis ECM (Error Correction Model). Hasil penelitian ini adalah dalam jangka panjang variabel harga emas, jumlah uang beredar, dan inflasi berpengaruh terhadap penerimaan dana zakat periode 2012-2019 di Baznas Pusat. Variabel nilai tukar tidak berpengaruh terhadap penerimaan dana zakat periode 2012-2019 di Baznas Pusat. Pada jangka pendek variabel jumlah uang beredar dan inflasi berpengaruh terhadap penerimaan dana zakat periode 2012-2019 di Baznas Pusat. Variabel harga emas dan nilai tukar tidak berpengaruh terhadap penerimaan dana zakat periode 2012-2019 di Baznas Pusat.